True friends : a tale from Tanzania - Kilaka, John, 1966- (Groundwood Books/ House of Anansi Press, 2006)
Elephant offers to store the grain of his best friend, Rat, in his house to stop thieves during a drought, but ends up stealing it himself, causing Rat, who is the only animal who knows how to make fire, to run away.